Results of fast neutron induced mutations in M1 and M2 generations of sorghum (Sorghum bicolour) - Pepó, Pál; Erdei, Éva (Acta Agraria Debreceniensis, 2007)
Due to climatic barriers, the genetic variability of Sorghum varieties decreases away from the gene centre, therefore hybrids cultivated in Hungary are restricted to a relatively limited genetic basis. This limited genetic basis results in a lower rate of genetic improvement, so the genetic basis of cytoplasm factors are to be extended. We enhanced the diversity of primary materials by fast neutron treatment. As a result of this treatment we detected sterile, deformed specimens with double panicles in the stock treated with a dose of 12.5 Gy in the M1 generation. Agronomically useful specimens were found in the stock treated with 10 Gy and 7.5 Gy doses, where the leaf area index (LAI) and Harvest- index gave higher values than those of the control group. In the stock treated with 5 Gy dose, variations were less significant. In the reseeded M2 generation we detected albino specimens with extreme chlorophyll defects in the 10 Gy Zádor stock.